Financial Access and Saving Behavior in Women Entrepreneurship Development - Zoel Hutabarat; Noah Rangi (Pandawan, 2026)
Women-owned businesses have become an important driver of economic growth, employment generation, and social inclusion, particularly in developing countries. Despite their growing contribution, women entrepreneurs continue to encounter barriers related to financial access, institutional support, and entrepreneurial capabilities. This study investigates how business support, access to finance, skill development, and saving behavior influence women entrepreneurship development among small and medium-sized enterprises in Batam City, Indonesia. Data were obtained from 244 women entrepreneurs and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The empirical results demonstrate that business support, financial access, and skill development positively affect women entrepreneurship development, with skill development emerging as the strongest predictor. In addition, saving behavior significantly moderates the relationship between access to finance and women entrepreneurship development, indicating that financial management practices influence the effectiveness of financial resources in supporting entrepreneurial growth. These findings suggest that sustainable women entrepreneurship depends on the interaction between external support mechanisms and individual entrepreneurial capabilities. The study provides practical implications for policymakers and entrepreneurship support institutions by emphasizing the importance of integrated strategies that strengthen financial inclusion, entrepreneurial competencies, financial literacy, and institutional support to foster the long-term development of women-owned enterprises.